2017
DOI: 10.1371/journal.pone.0181982
|View full text |Cite
|
Sign up to set email alerts
|

Comparative molecular analyses of invasive fall armyworm in Togo reveal strong similarities to populations from the eastern United States and the Greater Antilles

Abstract: The fall armyworm (Spodoptera frugiperda, J.E. Smith) is a noctuid moth that is a major and ubiquitous agricultural pest in the Western Hemisphere. Infestations have recently been identified in several locations in Africa, indicating its establishment in the Eastern Hemisphere where it poses an immediate and significant economic threat. Genetic methods were used to characterize noctuid specimens infesting multiple cornfields in the African nation of Togo that were tentatively identified as fall armyworm by mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
139
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(147 citation statements)
references
References 43 publications
7
139
0
1
Order By: Relevance
“…In comparison, the diagnostic rice strain Tpi marker, TpiR, was rarely found in all collections (frequency <0.06), consistent with earlier findings based on a survey of larval collections (Nagoshi et al, 2017b). However, fewer moths from bucket traps were COI-RS than COI-CS (v 2 = 9.4, P = 0.0028).…”
Section: Host Strain Marker Comparisonsupporting
confidence: 88%
See 1 more Smart Citation
“…In comparison, the diagnostic rice strain Tpi marker, TpiR, was rarely found in all collections (frequency <0.06), consistent with earlier findings based on a survey of larval collections (Nagoshi et al, 2017b). However, fewer moths from bucket traps were COI-RS than COI-CS (v 2 = 9.4, P = 0.0028).…”
Section: Host Strain Marker Comparisonsupporting
confidence: 88%
“…Larvae 74 (Nagoshi et al, , 2015, Texas, USA (TX) (Nagoshi et al, 2011), Florida, USA (FL) (Nagoshi et al, 2011), Puerto Rico (PR) (Nagoshi et al, 2015), Togo 2016 (larvae) (Nagoshi et al, 2017b), and Togo 2017 (traps) from this paper.…”
Section: Tpi-ca1mentioning
confidence: 99%
“…Recent studies have indicated that the molecular identification of the two strains of fall armyworm is dependent on which markers are used [35][36][37] . The early molecular markers based on mitochondrial Cytochrome Oxidase Subunit I (COI) and Z-chromosome-linked Triosephosphate isomerase (Tpi) genes failed to accurately assign strain identification [38][39][40][41] . The dominant population of fall armyworm invading Africa and Asia were speculated to be hybrid populations of the female R-strain and male C-strain, based on these two molecular markers 42 .…”
Section: Introductionmentioning
confidence: 99%
“…The rapid spread and establishment of H. armigera across much of the South American continent has generated a very large population with significant impacts on agricultural production. In contrast to usual invasions such as the African incursion of the New World fall armyworm S. frugiperda [16,34,[39][40][41][42], the invasive H. armigera population in the New World appears to be very diverse. Furthermore, the spatial distribution of this diversity strongly suggests that the population has spread from two different regions of introduction.…”
Section: Discussionmentioning
confidence: 97%